Sharpening Early Digital Literacy Skills as a Long-Term Investment for Young Children - Nur Amalina (State Institute of Islamic Studies Batusangkar, 2023)
AbstractIn today's rapidly advancing digital era, the ability to master technology has become crucial for everyone. Nearly all activities can be carried out using technology, especially digital technology that is accessible by anyone, anytime, and anywhere, from adults to young children. However, it's important to note that young children, who are in a crucial stage of growth and development, are highly susceptible to environmental influences, including digital technology which is now easily accessible to them, often with parental permission to use gadgets. Therefore, this is a significant concern because in the age range of 0-6 years, a child's brain development progresses rapidly, reaching up to 80%, allowing their brains to easily absorb various information, both positive and negative.This period is often referred to as the